If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (43x + -11y) + 5x = 0 Remove parenthesis around (43x + -11y) 43x + -11y + 5x = 0 Reorder the terms: 43x + 5x + -11y = 0 Combine like terms: 43x + 5x = 48x 48x + -11y = 0 Solving 48x + -11y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11y' to each side of the equation. 48x + -11y + 11y = 0 + 11y Combine like terms: -11y + 11y = 0 48x + 0 = 0 + 11y 48x = 0 + 11y Remove the zero: 48x = 11y Divide each side by '48'. x = 0.2291666667y Simplifying x = 0.2291666667y
| x^2+y^2-8x-9=0 | | x^2+6+36-x=90 | | 6+x+-3=4x+-8 | | 2x/x=24 | | c-0.85c=18 | | 3/28x8 | | 2r^2-131=0 | | x=4y+28 | | 210x^2-1680x+7700=0 | | (6x^3+5x^2-8x+9)+(17x^3+2x^2-4x-13)= | | 210x^2-1680+7700=0 | | y=14-2/3x | | 210x^2-1680+7700=6 | | -4x-2=-x-14 | | 21+9x=5x-7 | | 5x-8-7x=12 | | a-90=371 | | -0.5[X-4]=1.5 | | (-6x^3+5x^2-8x+9)(17x^3+2x^2-4x-13)= | | In(3x-1)=1 | | x/182=4 | | (x-3)(x+3)-(x-4)(4+x)=2x | | 9j^2+12j-12=0 | | n^2=9n-8 | | -40-8v=6(8v+3)+2v | | 39/78=x/6 | | 7y-2y=2 | | log[6]4x^2-log[6]x=2 | | a/20=6 | | 9-9x=1-7x | | http://www.thelearningodyssey.com | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/HSLQ_/HSLQ_AI13C02_T_stem2_1.gif |